At last [compact disc] - Evans, Luke, 1979-; Evans, Luke, 1979- (BMG Rights Management (UK) Ltd., 2019)
For his debut album as a music artist, Midway star Luke Evans has personally chosen an eclectic collection of modern and classic songs that highlight and complement his unique delivery and vocal style.